Intersubjectivity in action studies in language and social interaction - Lindström, Jan, 1964-; Laury, Ritva; Peräkylä, Anssi; Sorjonen, Marja-Leena (Pragmatics & beyond new seriess (P&BNS),, 2021)
"Intersubjectivity is a precondition for human life - for social organization as well as for individual development and well-being. Through empirical examination of social interactions in everyday and institutional settings, the authors in this volume explore the achievement and maintenance of intersubjectivity. The contributions show how language codes and creates intersubjectivity, how interactants move towards shared understanding in interaction, how intersubjectivity is central to phenomena and experiences often considered merely individual, and how intersubjectivity evolves through learning. While the core methodology of the studies is Conversation Analysis, the volume highlights the advantages of using several methods to tackle intersubjectivity"--